Pemberdayaan Masyarakat Melalui Ekonomi Usaha Kerajinan Tangan Penyulaman Noken - Funnisia Lamalewa; Elisabeth Lia Riani Kore (EKONOMI & SOSIAL, 2020)
The development of creative economy and encouraging community empowerment are the triggers of research which are expected to be able to describe the empowerment of Noken extension craftsmen with a focus on four key principles of empowerment development. This qualitative descriptive study involved informants using snowball sampling techniques, the results showed that empowerment did not work as it should and was not carried out in accordance with these principles, the failure to achieve the principle of equality supported by the justification of backing each party could participate as giving help to receive. The special program is designed from the executor of empowerment, designed by the community is still limited to mobilization so that it does not have the principle of participation. The principle of independence does not work because it is surrounded by a pattern of aid that does not support the form of independence and it is also realized that independence is only formed as a whole which begins with awareness, suspended with assistance, deferred with the assistance of craftsmen and deferred with craftsmen so that it can be done by delivering the economy. The implementation of this independence is not immediately approved for the release of assistance or in other words, the principle of sustainability is not implemented.